The Heterogeneity of Intralingual Translation - Hill-Madsen, Aage (Meta, 2019)
The aim of this article is to contribute to the establishment of a sub-field of translation studies, namely a sub-field devoted to the research of intralingual translation. The article’s contribution to this project is both theoretical and empirical. In the theoretical part of the article, an already existing, five-partite typology of intralingual translation is reviewed and on certain points refined. The empirical part is taken up by three case studies, each representing a particular subcategory of intralingual translation. The first study investigates translation between two geographical dialects (American and British English), the second examines the rewriting of a specialized, pharmaceutical product summary into a register aimed at lay readers, and the third investigates the modernization of one of Shakespeare’s plays. A primary concern of the case studies is to chart the range and nature of the translation strategies employed in the transformation of source texts into intralingual target texts. Translation strategies are conceptualized as shifts in the article, and well-known concepts from translation studies are applied in the analyses. The analytical results reflect clear differences, but also certain striking similarities between the types of shifts manifested in the individual cases.